Analisis Pengaruh Nilai Ekspor, Perbankan, dan Industri Otomotif Terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia (BEI) Periode 2013 – 2021 - Parulian Parulian; Emmelia Tan; Siti Amelia (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the effect of export value, banking, and the automotive industry on the Composite Stock Price Index (IHSG) at the Indonesia Stock Exchange (IDX) during the 2013–2021 period. The selection of this period was based on significant economic dynamics, such as fluctuations in the benchmark interest rate, the growth of national exports, and the impact of the COVID-19 pandemic on both the automotive industry and the capital market. A quantitative approach was employed using secondary quarterly data consisting of 36 samples, including the IHSG, export value, banking BI rate, and automotive industry GDP. Data analysis was conducted with SPSS version 22. The results indicate that export value has a positive and significant effect on the IHSG with a significance level of 0.001. The banking variable has a negative and significant effect on the IHSG with a significance level of 0.006, while the automotive industry shows no significant effect with a significance level of 0.644. Collectively, export value, banking, and the automotive industry explain 53.6% of the variation in the IHSG, as indicated by an adjusted R square of 0.536, while the remaining 46.4% is influenced by other variables not included in this study. These findings highlight the importance of export performance as the primary driver of IHSG movement, while the banking sector exhibits a more complex and negative influence. The automotive industry, however, does not show a significant relationship with the IHSG during the observed period.